Big Steps, Little Change: A Case Study in French University Teachers’ Cognitions in the Context of Pedagogical Innovation - Lami, Raphaël; Gastineau, Sylvie; Flom, Haley; Desdevises, Yves (Frontiers in Education, 2021)
The rate of failure of French students during their first years at university is substantial, with only 42% graduating in the expected three or four years. As a result, French universities have encouraged innovative teaching practices to improve undergraduate students’ academic success, notably the introduction of blended learning methods. In 2015, the three marine stations of Sorbonne Université created the online blended learning platform e-marin’lab for their marine science programs. In this paper, we sought to characterize the participating teachers’ cognitions with regard to teaching and learning (Borg, 2003; 1997). Despite the success of the project that relied on their substantial voluntary commitment, the teachers demonstrated an adhesion to more traditional views (i.e., directive teacher-student transmission of knowledge is more efficient for students’ learning). Perhaps more paradoxically, our data reveal that the same teachers saw themselves as teaching in a student-oriented way, and that their students’ lack of engagement in class was due to their poor study skills and intrinsic motivation. Among other factors that will be discussed, we believe that these results are influenced by a context that does not provide many teacher training opportunities and that places little importance on teaching in university professors’ career recognition. Finally, the importance of the e-marin’lab platform in the context of the SARS-CoV-2 pandemic situation from 2020 and the massive use of distance teaching in marine sciences during national lockdown periods is discussed.